The phosphopantetheinyl transferases: catalysis of a post-translational modification crucial for life - Beld, Joris; Sonnenschein, Eva C; Vickery, Christopher R; Noel, Joseph P; Burkart, Michael D (Natural product reports, 2014)
Covering: up to 2013. Although holo-acyl carrier protein synthase, AcpS, a phosphopantetheinyl transferase (PPTase), was characterized in the 1960s, it was not until the publication of the landmark paper by Lambalot et al. in 1996 that PPTases garnered wide-spread attention being classified as a distinct enzyme superfamily. In the past two decades an increasing number of papers have been published on PPTases ranging from identification, characterization, structure determination, mutagenesis, inhibition, and engineering in synthetic biology. In this review, we comprehensively discuss all current knowledge on this class of enzymes that post-translationally install a 4'-phosphopantetheine arm on various carrier proteins.